ENHANCING LEADERSHIP KNOWLEDGE THROUGH THE MINI MBA FOR SCHOOL LEADERS TRAINING PROGRAM - Syamril; Arohman, Mamat; Palupi, Palupi; Zaeni, Arpan (INQUISITIVE : International Journal of Economic, 2025)
Leadership knowledge is crucial for school leaders to build strong teams and achieve institutional goals. When this foundational knowledge is lacking, progress is often hindered. This study evaluates the effectiveness of the "Mini MBA for School Leaders" program in enhancing participants' understanding of leadership principles. Using a one-group pretest-posttest design with a sample of 29 school leaders, we measured the change in leadership knowledge following the training intervention. Data were analyzed using a normalized gain (N-gain) score. The results showed an average N-gain score of 0.59, indicating the program was "moderately effective" in increasing knowledge. These findings suggest that condensed, targeted training programs like the Mini MBA can be a valuable tool for professional development in the education sector, offering practical pathways to improve school management.